2019
DOI: 10.1089/ten.tea.2018.0191
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Localized Cold Therapy: A New Mode of Bone Repair Enhancement

Abstract: A variety of biological, mechanical, and physical therapeutic modalities of varying complexity, efficacy, cost, and safety profile have been developed to enhance bone healing. There have been sporadic reports of spontaneous bone formation after repeated cold exposure. In this study we report for the first time, the anabolic effect of cold exposure on bone healing in vivo resulting in a doubling of bone volume. Although the precise mechanism is not fully understood, cold is well known to stimulate osteoclastoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The sample size was determined heuristically based on previous studies by our team. 23,24 Shapiro-Wilk tests were used to confirm the assumption of normal distribution of the data. Quantitative data are expressed as means 6 SDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size was determined heuristically based on previous studies by our team. 23,24 Shapiro-Wilk tests were used to confirm the assumption of normal distribution of the data. Quantitative data are expressed as means 6 SDs.…”
Section: Discussionmentioning
confidence: 99%
“…A bilateral murine unicortical bone defect model was used to generate a reproducible, mechanically stable defect for intramembranous bone healing without the need for fixation. [19][20][21][22][23] The animal study was performed after approval by the McGill Facility Animal Care Committee and was conducted in accordance with the Canada Council on Animal Care. Skeletally mature male C57BL/6 mice were used as an animal model.…”
Section: Cortical Bone Defect Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in vitro studies showed that hypothermia could upregulated the key osteoblast transcription factor runt-related transcription factor 2 (Runx2) and osterix expression, resulting in the enhancement of osteoblasts bone formation (Aisha et al, 2014;Nie et al, 2015). Similarly, effects of cold exposure on bone repair and bone formation were also observed through in vivo studies (Galliera et al, 2013;Castano et al, 2019).…”
Section: Introductionmentioning
confidence: 94%